'The Jigsaw Culture of Care': A qualitative analysis of Montessori-Based programming for dementia care in the United Kingdom. (November 2021) - Raghuraman, Shruti; Tischler, Victoria
Aims: Montessori-Based Programming (MBP) in dementia care refers to a growing body of research and practice that has developed Montessori methods to facilitate self-paced learning, independence and engagement for people living with dementia. A number of research gaps have been identified in the existing literature such as a lack of cross-cultural studies and well-powered, robustly designed outcome studies. The current study investigated the use of MBP with a focus on provision in the United Kingdom. It aimed to identify MBP implementation approaches, challenges and barriers, and research gaps. Design and Methods: A qualitative design was implemented to analyse data from in-depth, semi-structured interviews with key stakeholders ( N = 8) with experience of MBP in the UK. Participants included care home management and staff, MBP trainers and independent dementia experts with a background in Montessori methods. Thematic analysis identified 4 main themes and 12 sub-themes. The study took place between April 2019 and October 2019. Findings: A framework describing knowledge and understanding of MBP in the UK, implementation considerations, challenges and barriers, evidence of outcomes and research gaps was developed to provide guidance for researchers and practitioners. Implementation considerations included using a whole-home approach and changing the culture of care through management support. Barriers to implementation included conservative attitudes to care, perceived lack of time and resources, health and safety issues, and issues of sustainability. Conclusion: The benefits of MBP in dementia care are promising but require further empirical investigation. There is a need to design, execute and publish evidence to secure the support of key stakeholders in dementia care research, policy and commissioning in the UK.